2020
DOI: 10.1177/0361198120924008
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of High-Speed Railway Geosynthetic Reinforced Pile-Supported Embankment Subjected to Traffic Loading Considering Arching Effect

Abstract: Geosynthetic reinforced pile-supported (GRPS) embankment is widely used in the construction of high-speed railways on soft foundations. Arching effect, which is a common phenomenon in the system involving soil-structure interaction, is considered a key factor in the design of GRPS embankment. Its performance has been found inevitably to affect the post-construction settlement and bearing capacity of the embankment. However, the existing design methods are mainly based on static loading condition; soil arching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, it has been an important endeavor for geotechnical specialists to examine the performance of rigid foundations and pavements resting on reinforced soil beds. A notable improvement in the performance of various structures, such as pavements, railroad tracks, and foundations, constructed on reinforced soil beds was confirmed by a few researchers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Under seismic conditions, the reinforced soil bed was also reported to perform exceptionally well (13)(14)(15).…”
mentioning
confidence: 83%
“…Thus, it has been an important endeavor for geotechnical specialists to examine the performance of rigid foundations and pavements resting on reinforced soil beds. A notable improvement in the performance of various structures, such as pavements, railroad tracks, and foundations, constructed on reinforced soil beds was confirmed by a few researchers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Under seismic conditions, the reinforced soil bed was also reported to perform exceptionally well (13)(14)(15).…”
mentioning
confidence: 83%
“…The static and dynamic performance of GRPS embankment was investigated Bi et al [22] numerically, the researchers observed that the SCR decreases under longterm traffic loads and the stiffness of the soft soil has a main role in undermining the performance of soil arching. They observed also that the differential settlements increase with the cycles number to finally be in a stable state.…”
Section: Introductionmentioning
confidence: 99%